O papel narrativo da canção nos filmes brasileiros a partir da Retomada - Silva, Edison Delmiro (2008)
From the analysis of sixty-two Brazilian movies released since 1995, the thesis presents a categorization of the narrative role of popular songs in these productions. The films of this period called "Retomada (National Cinema Resume) show the use of this specific musical form for the construction of meanings in scenes and, ultimately, for the making of allegories that form a contemporary cultural identity and renew the concept of nationality represented in cinema. The study applies the analytical paradigms of the audiovisual soundtrack to the context of the song, categorizes its functions narratives with examples taken from Brazilian movies and observes the historical periods where the song was highlighted in Brazilian films, from the silent movies to the latest musical films